2009
DOI: 10.1111/j.1471-0528.2008.02082.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart disease – why is maternal mortality increasing?

Abstract: Please cite this paper as: Gelson E, Gatzoulis M, Steer P, Johnson M. Heart disease -why is maternal mortality increasing ? BJOG 2009;116:609-611. The most recent triennial confidential enquiry confirmed that heart disease is the most common cause of maternal death in the UK. The maternal mortality rate associated with heart disease is 2.27 per 100,000 maternities double that reported in 1990. 1 The incidence of heart disease during pregnancy in the UK has remained constant at 0.9% over several decades. 2 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…In the studies conducted, it has been revealed that serious increases have occurred in maternal mortality rates (6,12,13). Especially, parturients with cyanotic heart disease, cardiomyopathy, aortic and mitral valve stenosis, mechanic valvular diseases and pulmonary hypertension constitute the highest-risk group (6).…”
Section: Discussionmentioning
confidence: 99%
“…In the studies conducted, it has been revealed that serious increases have occurred in maternal mortality rates (6,12,13). Especially, parturients with cyanotic heart disease, cardiomyopathy, aortic and mitral valve stenosis, mechanic valvular diseases and pulmonary hypertension constitute the highest-risk group (6).…”
Section: Discussionmentioning
confidence: 99%
“…As sepsis has fallen in frequency over time, thromboembolism and underlying cardiac disease, especially cardiomyopathies, have taken over the lead positions. The surprising emergence of cardiac disease has also been seen in Great Britain [14 ] and the Netherlands [15 ] and may partially reflect better recognition and attribution of what was formerly known as 'indirect' causes. Obstetric hemorrhage remains an important cause of maternal mortality even in the modern era.…”
Section: Causesmentioning
confidence: 99%
“…As one of the themes of this review, maternal mortality is not a single diagnosis and so we should approach each cause individually. An approach to reducing obstetric hemorrhage will be focused on labor and delivery systems and teamwork [24 ]; reducing venous thromboembolism will focus more simply on DVT prophylaxis [25 ] and less simply on obesity reduction; reducing deaths from cardiac disease will involve education for earlier recognition and effective multidisciplinary care [14 ]. Even the overwhelming coagulopathy from amniotic fluid embolism (AFE) has shown some responsiveness to massive transfusion protocols and r-Factor VIIa [26 ].…”
Section: What Can We Do?mentioning
confidence: 99%
“…сти в последние годы имеет парадоксальную тенденцию к возрастанию [3,4]. Так, в США материнская смертность, обусловленная сердечно-сосудистыми заболеваниями, в 1987-1990 гг.…”
unclassified